Pengaruh Variasi Produk Terhadap Keputusan Pembelian Pada Konsumen Gen Z di Kopi Kenangan Kota Solo - Shabilla Chaqqiafni; Muhammad Syihabuddin (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the effect of product variation on purchasing decisions among Generation Z consumers of Kopi Kenangan in Solo City. The research is motivated by the rapid growth of the modern coffee industry and the changing behavior of young consumers who tend to prefer innovative and diverse products. This study employs a quantitative approach with an associative research design. Data were collected through questionnaires distributed to 100 respondents using purposive sampling technique. The data were analyzed using simple linear regression with the assistance of SPSS software. The results indicate that product variation has a positive and significant effect on purchasing decisions, with a significance value of 0.000 < 0.05 and a coefficient of determination of 0.470. This means that product variation explains 47% of purchasing decisions, while the remaining is influenced by other variables outside the model. These findings suggest that greater product diversity increases consumers’ likelihood to make purchases. This study implies that businesses should continuously develop innovative product variations aligned with the preferences of Generation Z consumers.